Why Diabetes Worsens Patient Prognosis: A Literature Review of Cardiovascular and Renal Complications - Rafałowicz, Magdalena; Rafałowicz, Adam; Wojciechowska, Urszula, Justyna; Mierzejewski, Jakub (Quality in Sport, 2025)
Background. Diabetes is considered a serious chronic metabolic disease due to its increasing prevalence worldwide. The main factor worsening the prognosis of patients is cardiovascular complications, which are the main factors of morbidity and mortality in diabetes. Aim. This review aims to explain why diabetes exacerbates cardiovascular and renal diseases, leading to worse clinical outcomes in affected individuals, focusing on its pathophysiological mechanisms. Material and Methods. A systematic literature review was conducted using PubMed and Google Scholar databases. Meta-analyses, randomized controlled trials, cohort studies, and systematic reviews regarding the impact of diabetes on arrhythmogenesis, myocardial ischemia, stroke, venous thromboembolism and the development of chronic kidney disease were analysed. Results. Cardiac arrhythmias have been shown to be promoted by glycaemic variability and autonomic neuropathy. Based on the research, we can conclude that the increased risk of myocardial infarction and ischemic stroke is due to persistent hyperglycaemia, which, by inducing oxidative stress and chronic inflammation, leads to endothelial dysfunction and plaque instability. Based on the accumulated evidence, we know that the association between diabetes and venous thromboembolism remains inconsistent. Diabetes significantly increases the risk and worsens patients outcomes after ischemic stroke, mainly by increasing the risk of ischemic focus haemorrhagic and reducing cortical plasticity. The effect of diabetes on the course of haemorrhagic stroke is not unequivocal. Diabetic kidney disease increases the risk of cardiovascular disease. Conclusion. The multifactorial effects of hyperglycaemia on both the cardiovascular system and chronic kidney disease synergistically worsen outcomes in diabetes. Early detection, rigorous glycaemic control, and multifaceted management of risk factors are essential to improve survival.